Programmable RNA-Guided Large DNA Transgenesis by CRISPR/Cas9 and Site-Specific Integrase Bxb1 - Hosur, Vishnu; Low, Benjamin E.; Wiles, Michael V. (Frontiers in Bioengineering and Biotechnology, 2022)
The inability to insert large DNA constructs into the genome efficiently and precisely is a key challenge in genomic engineering. Random transgenesis, which is widely used, lacks precision, and comes with a slew of drawbacks. Lentiviral and adeno-associated viral methods are plagued by, respectively, DNA toxicity and a payload capacity of less than 5 kb. Homology-directed repair (HDR) techniques based on CRISPR-Cas9 can be effective, but only in the 1 to 5 kb range. In addition, long homology arms—DNA sequences that permit construct insertion—of lengths ranging from 0.5 to 5 kb are required by currently known HDR-based techniques. A potential new method that uses Cas9-guided transposases to insert DNA structures up to 10 kb in length works well in bacteria, but only in bacteria. Surmounting these roadblocks, a new toolkit has recently been developed that combines RNA-guided Cas9 and the site-specific integrase Bxb1 to integrate DNA constructs ranging in length from 5 to 43 kb into mouse zygotes with germline transmission and into human cells. This ground-breaking toolkit gives researchers a valuable resource for developing novel, urgently needed mouse and human induced pluripotent stem cell (hiPSC) models of cancer and other genetic diseases, as well as therapeutic gene integration and biopharmaceutical applications, such as the development of stable cell lines to produce therapeutic protein products.